2020
DOI: 10.3389/fbioe.2020.00171
|View full text |Cite
|
Sign up to set email alerts
|

Anticipating Xenogenic Pollution at the Source: Impact of Sterilizations on DNA Release From Microbial Cultures

Abstract: The dissemination of DNA and xenogenic elements across waterways is under scientific and public spotlight due to new gene-editing tools, such as do-it-yourself (DIY) CRISPR-Cas kits deployable at kitchen table. Over decades, prevention of spread of genetically modified organisms (GMOs), antimicrobial resistances (AMR), and pathogens from transgenic systems has focused on microbial inactivation. However, sterilization methods have not been assessed for DNA release and integrity. Here, we investigated the fate o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…With increased automation, dangers arise, for example, in the context of sterilization methods used in the healthcare and laboratory setting. For some methods, a very recent study [ 62 ] demonstrates that “integrity of released DNA is not completely compromised,” which is leading to the “danger of dissemination of DNA and xenogenic elements across waterways.” These findings were linked to temperature and time (e.g., short microwave exposure times or short exposure time to glutaraldehyde treatment were least effective). Parameters like these are both highly malleable and susceptible to manipulation, which will become an even bigger concern with “smart labs” of the future [ 21 ].…”
Section: Pressing and Unique Dangers And Consequencesmentioning
confidence: 99%
“…With increased automation, dangers arise, for example, in the context of sterilization methods used in the healthcare and laboratory setting. For some methods, a very recent study [ 62 ] demonstrates that “integrity of released DNA is not completely compromised,” which is leading to the “danger of dissemination of DNA and xenogenic elements across waterways.” These findings were linked to temperature and time (e.g., short microwave exposure times or short exposure time to glutaraldehyde treatment were least effective). Parameters like these are both highly malleable and susceptible to manipulation, which will become an even bigger concern with “smart labs” of the future [ 21 ].…”
Section: Pressing and Unique Dangers And Consequencesmentioning
confidence: 99%
“…On the other side, the fate of residual genomic DNA from dead cells following heat treatments remains questionable, taking into account that three studies showed that autoclave sterilization (121 • C/15 min), which is chemically more stringent than UHT sterilization, did not totally degrade DNA (Masters et al, 1998;Yap et al, 2013;Calderón-Franco et al, 2020). By considering a 10 5 cfu/ml raw milk sample, a rough estimation lead to around 24,500 AMR genes per ml of raw milk (Munsch- .…”
Section: Food Production Systems and Antimicrobial Resistance: Milk Is Also A Concernmentioning
confidence: 99%
“…Extracellular DNA (exDNA) is commonly released from the intracellular DNA (iDNA) during cell lysis (passive release) or excreted from live cells (active release). 20,21 Such exDNA can be present as a structural component in microbial aggregates, as part of the matrix of extracellular polymeric substances (EPS) 22 or floating freely in the water body. 23 Recent advances in methods for the extraction of exDNA allow for a deeper analysis of the composition and distribution of both DNA fractions in WWTPs and natural environments.…”
Section: Introductionmentioning
confidence: 99%